2023
DOI: 10.1038/s41467-023-39084-2
|View full text |Cite
|
Sign up to set email alerts
|

Origin of minicircular mitochondrial genomes in red algae

Abstract: Eukaryotic organelle genomes are generally of conserved size and gene content within phylogenetic groups. However, significant variation in genome structure may occur. Here, we report that the Stylonematophyceae red algae contain multipartite circular mitochondrial genomes (i.e., minicircles) which encode one or two genes bounded by a specific cassette and a conserved constant region. These minicircles are visualized using fluorescence microscope and scanning electron microscope, proving the circularity. Mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 156 publications
0
2
0
Order By: Relevance
“…Similar outcomes have been documented for all G. angusta, G. cornea, G. elliptica, G. filicina, and G. taiwanensis , but not for P. affinis and P. lancifolius ( Table 1 ) [ 6 , 7 , 8 , 9 , 10 , 11 ]. Group II intronic cox1 and trnI are the unique features of red algal mitogenomes [ 12 , 13 , 15 ]. The ymf39 gene is transcribed between cox3 and trnG genes in the mitogenome of G. turuturu and encodes an ATP synthase B chain precursor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar outcomes have been documented for all G. angusta, G. cornea, G. elliptica, G. filicina, and G. taiwanensis , but not for P. affinis and P. lancifolius ( Table 1 ) [ 6 , 7 , 8 , 9 , 10 , 11 ]. Group II intronic cox1 and trnI are the unique features of red algal mitogenomes [ 12 , 13 , 15 ]. The ymf39 gene is transcribed between cox3 and trnG genes in the mitogenome of G. turuturu and encodes an ATP synthase B chain precursor.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively little is known about the mitogenome of Rhodophytes, and due to advancements in software and molecular technologies, more and more detailed studies are being reported. In fact, red algal mitogenomes are more complete than previously reported [ 12 ], and it has also been reported that red algae, Strylonematophyceae , contain multiple minicircular mitochondrial genomes that encode one or two genes [ 13 ]. These studies are made possible by applying bundles of software tools.…”
Section: Introductionmentioning
confidence: 99%
“…Minicircles, almost corresponding to individual mtDNA genes, have been recently reported in red algae (Y. Lee et al, 2023). The euglenozoan Diplonema papillatum has multiple small mtDNA fragments smaller than the size of individual genes, which must be spliced together from these fragments (Vlcek et al, 2011).…”
Section: Specific Strategies Across Eukaryotesmentioning
confidence: 99%